2017
DOI: 10.1021/acs.jafc.7b03361
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-Mediated Anti-Apoptotic Effect of Ginsenoside Rg5, a Main Rare Ginsenoside, on Acetaminophen-Induced Hepatotoxicity in Mice

Abstract: Frequent overdose of acetaminophen (APAP) is one of the most common and important incentives of acute hepatotoxicity. Prior to this work, our research group confirmed that black ginseng (Panax ginseng, BG) showed powerful protective effects on APAP-induced ALI. However, it is not clear which kind of individual ginsenoside from BG plays such a liver protection effect. The objective of the current investigation was to evaluate whether ginsenoside Rg5 (G-Rg5) protected against APAP-induced hepatotoxicity and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 55 publications
3
47
1
Order By: Relevance
“…In addition, BNIP3 caused apoptosis and promoted Bax/Bad-dependent release of pro-apoptotic mediators [ 39 ]. Present results revealed that APAP injection downregulated Bcl-2 and upregulated Bax, and cleaved caspase 3 protein expression in hepatocytes, which was in line with our previous studies [ 23 ]. Importantly, supplementation of α-MG partially maintained the balance between Bax and Bcl-2, resulting in the prevention of mitochondrial dysfunction caused by APAP.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, BNIP3 caused apoptosis and promoted Bax/Bad-dependent release of pro-apoptotic mediators [ 39 ]. Present results revealed that APAP injection downregulated Bcl-2 and upregulated Bax, and cleaved caspase 3 protein expression in hepatocytes, which was in line with our previous studies [ 23 ]. Importantly, supplementation of α-MG partially maintained the balance between Bax and Bcl-2, resulting in the prevention of mitochondrial dysfunction caused by APAP.…”
Section: Discussionsupporting
confidence: 93%
“…For the histology examination, liver samples were fixed immediately with neutral buffered formalin solution. Liver sections (5 μm thickness) were prepared from paraffin-embedded tissue and subjected to H&E staining for further histological analysis under a light microscope (100× and 400×) [ 23 ]. The necrotic degree (as a percentage of the total area) was assessed by the necrotic area, inflammatory cell infiltration degree, and congestion relative to the entire histological sections.…”
Section: Methodsmentioning
confidence: 99%
“…Under normal circumstances, apoptosis is a permanent and fundamental form of programmed cell death that occurs in multicellular organisms [ 8 ]. Although apoptosis is a regular biological phenomenon, acute cellular injury also can trigger defective apoptosis and further touch off tissue necrosis in CDDP-induced AKI [ 9 ]. It was reported that oxidative stress and inflammation are also leading factors in CDDP-induced nephrotoxicity [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Certain to-date unknown components of rosemary inhibit PTEN expression in K562 myeloid cells (70) and rosemary promotes liver regeneration in an experimental injury model (69). In contrast, levels of PTEN are increased when treated with Ginsenoside, a class of natural steroid glycosides, which exhibit hepatoprotective effects against acute hepatotoxicity in mice (71). Furthermore, certain types of diet rich in fat or carbohydrates contribute to hepatocyte protection (72).…”
Section: Diet and Hepatocyte Protectionmentioning
confidence: 99%